STRATEGI PENGEMBANGAN WISATA HIU PAUS DALAM UPAYA PENINGKATAN PENDAPATAN MASYARAKAT DESA LABUHAN JAMBU KECAMATAN TARANO KABUPATEN SUMBAWA - Wahyuni, Yayu Dwi; Hailuddin, Hailuddin; Wahyunadi, Wahyunadi (Jurnal Konstanta, 2025)
This study aims to analyze whale shark tourism development strategies in an effort to increase the income of the Labuhan Jambu Village community and to determine what factors influence the development of the Saleh Bay whale shark tourism attraction. This study is a qualitative study with a descriptive approach. Data were collected through interviews and analyzed using a SWOT analysis to generate alternative strategies. The results of the study indicate that based on the SWOT coordinate diagram, Saleh Bay whale shark tourism is in quadrant I (positive-positive) with the SWOT coordinate point at the position (0,13 : 0,62). This value indicates that Saleh Bay whale shark tourism has quite good internal strengths and significant external opportunities. Therefore, based on these results, alternative S-O strategies that can be implemented are the use of social media and digital technology, increasing collaboration to expand tourism reach, empowering local human resources, combining tourist destinations in one package, and developing tourist packages with additional tourism activities.